2012
DOI: 10.9775/kvfd.2012.5975
|View full text |Cite
|
Sign up to set email alerts
|

Biberiye ve Kekik Esansiyel Yağları Katkısının Marine Edilmiş Kerevitlerin (Astacus leptodactylus Esch., 1823) Raf Ömrüne Etkisinin Belirlenmesi

Abstract: ÖzetBu çalışmada, biberiye ve kekik esansiyel yağları uygulanarak marine edilen kerevitlerin 4ºC'de muhafazası sırasında kimyasal [pH ve tiyobarbitürik asit (TBA)], mikrobiyolojik (Toplam aerobik bakteri, psikrofilik bakteri, laktik asit bakterileri ve maya küf bakteri sayımı) ve duyusal niteliklerinde meydana gelen değişimler incelenmiştir. Analiz sonuçlarına göre gruplar arasında pH değeri bakımından istatistiksel olarak fark saptanmamıştır (P>0.05). Ancak TVB-N ve TBA miktarları açısından kontrol grubu ile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In a previous study, the crawfish meat marinated with thyme and rosemary essential oils were stored at 4℃ for 10 days, and at the end of the storage period, the LAB numbers of samples containing rosemary and thyme essential oils were found to be lower than that of control sample (Duman et al, 2012). In that study, LAB numbers of samples containing rosemary and thyme essential oils were 5.91 and 4.93 log CFU/g, respectively, and it was reported that the thyme essential oil was found to be more effective on the inhibition of LAB when compared with the rosemary essential oil.…”
Section: Microbiological Analysis Resultsmentioning
confidence: 88%
“…In a previous study, the crawfish meat marinated with thyme and rosemary essential oils were stored at 4℃ for 10 days, and at the end of the storage period, the LAB numbers of samples containing rosemary and thyme essential oils were found to be lower than that of control sample (Duman et al, 2012). In that study, LAB numbers of samples containing rosemary and thyme essential oils were 5.91 and 4.93 log CFU/g, respectively, and it was reported that the thyme essential oil was found to be more effective on the inhibition of LAB when compared with the rosemary essential oil.…”
Section: Microbiological Analysis Resultsmentioning
confidence: 88%
“…An increase was observed in the amount of LAB in all of the groups throughout the storage duration. Duman et al (2012) emphasized that the amount of LAB in the rosemary and thyme oil added groups were lower than the control group. Patır et al (2015) reported that the amount of LAB in marinated trout (O. mykiss) with eugenol-added samples were lower than the control group.…”
Section: Resultsmentioning
confidence: 92%
“…Erkan et al (2011) emphasized that the laurel and cinnamon ail applications on the bluefish were effective on the amount of TPAB. In the study of Duman et al (2012), rosemary and thyme oil were applied on marinated crayfish and it was reported that the amount of TPAB was higher in the control group than the essential oil added groups. Our study is similar to the findings of this research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the harmful effects of synthetic substances on health, their use is limited and the tendency toward natural additives has increased day by day. [ 18–20 ] Numerous plant species (rosemary, thyme, sage, clove, and garlic) have been used as natural antioxidant sources in fisheries. [ 21–24 ] Citrus (Rutaceae) oils including lemon, orange, mandarin, and grapefruit also have high antimicrobial and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%